Griffith's 5-minute clinical consult 2005 - Dambro, Mark R.; Dambro, Mark R. (Philadelphia : Lippincott Williams & Wilkins, 2005)
(Producer) Allows the user to access current ICD-9 codes and drug information as well as review diagnostic protocol and treatment options on over 1,000 of the most common medical-surgical problems encountered in a primary care setting.
Title from disc label.
Keywords: Clinical Medicine